An approximation method for evaluating the reliability of a dynamic k-out-of-n:F system subjected to cyclic alternating operation conditions. (April 2017) - Lin, Cong; Cui, Lirong; Coit, David; Lv, Min
This article extends the finite Markov chain imbedding approach to evaluate the system reliability of a dynamic k -out-of- n :F system operating under two cyclic alternating conditions, and this article presents a method to obtain the optimal replacement interval of the system according to age-based replacement policy. In terms of the "dynamic k -out-of- n :F" model, we regard the system as two distinct k -out-of- n :F systems with different values of k while the system is operating under each condition. We apply the proposed model to analyze the reliability of a wireless sensor network, whose sensors switching into sleep state to save energy and shifting into listen state to detect the information alternatively. We also obtain the optimal replacement interval to redeploy the wireless sensor networks.